SIKAP TASĀMUH DALAM PENDIDIKAN MULTIKULTURAL - Rahma Maulida (Universitas Islam Negeri Ar-Raniry, 2013)
This research was conducted at International Elementary School Bunga Matahari,Banda Aceh for its homogeneity, both tribes, nations and religions. This diversity is interesting to have a further study in order to know the process of tolerance guiding in multicultural education. The results of the study show that there are some tasāmuh (tolerance) attitudes in multicultural education as mutual helps, mutual respects, mutual communications, mutual care, not to blame others, not to be selfish and inclusive. The tolerance attitudes which have been conducting at International Elementary School Bunga Matahari,Banda Aceh is in accord with the Islamic education system, but in the teaching of religious education for non-Muslims, not in accordance with the perspective of Islamic the education, the learning process is still discriminatory. The leading factors in supporting the tolerance implementation in multicultural education at National Elementary Bunga Matahari, Banda Aceh are dialogue, egalitarianism, impartiality, the 1945 Constitution, Article 29, 2nd paragraph, multicultural education which contains the values of pluralism and tolerance attitudes towards diversity. The inhibiting factors in developing tolerance attitudes are exclusiveness, learning model which tends to be dogmatic, religion is directed into not free variable, the solution of developing tolerance is that the educational implementation should be oriented on the value that will provide pressure point on how students see, understand, and face the diversity of life in multicultural education.